Profile Saturation Learning of Student in Senior High Scholl 8 Padang - Sari Murti; Yusri Yusri (Jurnal Neo Konseling, 2019)
Saturation of learning is a condition in which students feel bored, tired, lack of attention in lessons, no interest and motivation in learning and do not bring results. In fact there are still students who experience saturation in learning. This study aims to describe (1) Saturation Learning of Student in Senior High Scholl 8 Padang based on aspects of emotional fatigue, (2) Saturation Learning of Student in Senior High Scholl 8 Padang based on aspects of physical fatigue, (3) Student learning saturation in Padang 8 High School based on aspects cognitive fatigue, (4) Saturation Learning of Student in Senior High Scholl 8 Padang based on aspects of motivation loss. This study uses quantitative methods with descriptive research types. The population of this research is the students of  Senior High Scholl 8 Padang in class X and XI with a total of 603 students. With a sample of 240 students selected using the proportional random sampling technique. The instrument used in this study was a questionnaire. Data is processed using percentage techniques. The results of this study indicate that Saturation Learning of Student in Senior High Scholl 8 Padang is in a more detailed low category  (1) Saturation Learning of Student in Senior High Scholl 8 Padang based on aspects of emotional fatigue is in the low category, (2) Saturation Learning of Student in Senior High Scholl 8 Padang based on aspects of physical fatigue are in the low category, (3) Saturation Learning of Student in Senior High Scholl 8 Padang based on aspects of cognitive fatigue are in the low category, (4) Saturation Learning of Student in Senior High Scholl 8 Padang based on aspects of motivation loss is in the low category.